Foodie Calls: When Women Date Men for a Free Meal (Rather Than a Relationship). Issue 3 (April 2020) - Collisson, Brian; Howell, Jennifer L.; Harig, Trista
A foodie call occurs when a person, despite a lack of romantic attraction to a suitor, chooses to go on a date to receive a free meal. The present study examines predictors of a deceptive form of the foodie call in the context of male–female dates: when a woman purposefully misrepresents her romantic interest in a man to dine at his expense. In two studies, we surveyed women regarding their foodie call behavior, dark triad personality traits, traditional gender role beliefs, and online dating history. We found 23–33% of women surveyed had engaged in a foodie call. In Study 1, dark triad and traditional gender role beliefs significantly predicted previous foodie call behavior and its perceived acceptability. Study 2 employed fuller measures and suggested again that dark triad traits predicted foodie calls and their perceived acceptability.